1993
DOI: 10.1002/cyto.990140114
|View full text |Cite
|
Sign up to set email alerts
|

Cytometric analysis of blood cells from malaria‐infected patients and in vitro infected blood

Abstract: Blood samples from malaria-infected patients and from in vitro culture were analyzed using the H*l hematology analyzer. An attempt to find a hematologic parameter for detecting the malaria infection and to characterize the pathophysiological changes of red cells was made. The study included 18 malaria-infected patients (10 with Plasmodium falciparum and 8 with Plasmodium viva.4 and 52 normal, healthy volunteers. Increased young large lymphocyte or large unstained cell count (LUC over 3%) in the peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…A high sensitivity (81%) and specificity (87%) was seen along with an increase in probability of malaria by factor 6.2, in concurrence with observations by other authors. 19 Although the role of RDW in the diagnosis of malaria is debatable, the presence of increased RDW has correlated well with the percentage of macrocytes in one study, 30 hence a combination of RDW and MCV may be more helpful. 28 Dhungat et al concluded that although a reliable diagnostic marker, there is no prognostic significance of thrombocytopenia in malarial fevers.…”
Section: Discussionmentioning
confidence: 96%
“…A high sensitivity (81%) and specificity (87%) was seen along with an increase in probability of malaria by factor 6.2, in concurrence with observations by other authors. 19 Although the role of RDW in the diagnosis of malaria is debatable, the presence of increased RDW has correlated well with the percentage of macrocytes in one study, 30 hence a combination of RDW and MCV may be more helpful. 28 Dhungat et al concluded that although a reliable diagnostic marker, there is no prognostic significance of thrombocytopenia in malarial fevers.…”
Section: Discussionmentioning
confidence: 96%
“…In 1993, a study analysing 18 samples from patients with malaria ( P. falciparum: 10 and P. vivax : 8) and 52 samples from healthy controls with a Technicon H1 ® analyser (Technicon Instruments Corporation, Tarry Town, NY; now Siemens), found that all malaria-infected patients had ≥3% (range 3.3-20.9%) of so-called 'large-unstained-cells' suggesting their potential use for malaria screening [25]. Unfortunately, changes in WBC populations [26], reticulocytosis, or increase of 'large-unstained-cells' [25] may also appear with other pathologies, giving these changes low accuracy for malaria detection.…”
Section: Discovery Of Automated Haematology Analysers For Malaria Diamentioning
confidence: 99%
“…The same mechanism however cannot be said to be associated with RDW increase in P. falciparum infection since parasitized cells maintain their sizes [29]. The elevated RDW seen in this study could result from the bone marrow’s effort to balance erythrocytes loss in malaria by pushing more new erythrocytes into circulation which also increases the macrocyte percentage [30, 31]. …”
Section: Discussionmentioning
confidence: 93%